Sintesis dan Karakterisasi Magnetik Nanopartikel NiFe2O4 Menggunakan Ekstrak Kulit Buah Naga (Hylocereus Polyrhizus) - Srifu Rahmawita; Alizar Ulianas (Departemen Kimia FMIPA UNP, 2021)
In the past few years, intensive research has been carried out on magnetic nanoparticles, one of which is ferrite nanoparticles. These ferrite nanoparticles have the general formula MFe2O4 (where M = Mn, Co, Zn, Cu, and Ni). This nanoparticle is interesting because it has magnetic properties and is more efficient than other ferrite nanoparticles in its application. This research was conducted to synthesize NiFe2O4 nanoparticles with a hydrothermal method based on green chemistry by utilizing dragon fruit peel extract as a stabilizing agent. NiFe2O4 nanoparticles were characterized with a Gauss meter to measure their magnetic strength, FTIR, XRD and SEM were used to determine functional groups, particle size, and surface morphology of the nanoparticles. The greatest magnetic strength of magnetic nanoparticles is 0.19 mT with a composition of 25 mL dragon fruit peel extract, 2 mol Fe(NO3)3.9H2O and 1 mol Ni(NO3)2.6H2O. The FTIR test showed the presence of an OH group absorption peak at a wavelength of 3359.93 cm-1, the C = C group appeared at a wavelength of 1631.03 cm-1 and the C-O group at a wavelength of 1360.20 cm-1, which indicates that NiFe2O4 nanoparticles are protected by organic compounds (flavonoids ). Characterization of magnetic nanoparticles using XRD showed the shape of the nanoparticles produced in the form of cubic spinels with a particle size of 71.52 nm, while SEM characterization showed surface shapes such as irregular fine grains.